Agricultural Development of Eastern Europe Countries: Investments in this Sector their way out of Crisis: Case of Albania - Ilir Binaj; Dudie Suli (International Journal of Economics and Financial Issues, 2013)
This paper emphasizes the vital importance of the agriculture sector to the food security for Albania and other neighboring post-communist countries. The aim of this study is to illustrate how investments in agricultural development and food security can protect these countries form future global crisis. Agriculture sector used to be a major contributor to the Albanian economy until the 90’s and its role decreased with the liberalization of the economy. Albanians are of the opinion that more investment opportunities within the agricultural sector are required to decrease poverty at the national level and to make sustainable development possible for Albania. To achieve this, agricultural development and food security must be at the focus of the Albanian economy. This paper recommends an increase in investment within the agricultural sector across the nation. The mixed research approach method was used to validate these claims.